Responsivitas Pelayanan Unit Gawat Darurat di Puskesmas Jabiren - Hamberi Hamberi; Dwi Rohmiatun (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2017)
This study aims to examine and explain the Responsiveness of Emergency Unit Services (UGD) at Jabiren Health Center, Pulang Pisau Regency. The research method used is descriptive qualitative because the problems brought by researchers are still unclear in nature and are holistic (overall) sources of data in this study consisting of primary and secondary data which is the primary data is the head of Jabiren Health Center, midwife, nurse / officer- medical staff, and the community who received ED services at the Jabiren Health Center. Data collection techniques in this study are observation, interview, and documentation. Based on the results of the survey that the responsiveness of emergency services in Jabiren Health Center is known to be still not optimal because nurses/midwives often do not deliver on time in the ED services, there have been mistakes during the health care process, medicines are still lacking, human resources are still lacking, and there are still facilities for supporting facilities at the ER.